Women’s Sartorial Freedom and Educational Rights in Shelina Janmohamed’s Love in a Headscarf - Raihan Rosman (Asiatic: IIUM Journal of English Language and Literature, 2023)
The position of Muslim women is much debated, as they are often perceived as oppressed, subjugated, and victims of patriarchal society. However, Islam ensures women’s dignity as equal human beings. Nevertheless, cultural expectations and the multiplicity of interpretations of Islamic teachings lead to various conventions, practices, and beliefs that limit women’s rights. Based on this observation, this paper explores Muslim women’s sartorial liberty and right to education as depicted in Shelina Zahra Janmohamed’s Love in a Headscarf. It emphasises the distinction between the Islamic faith and Muslim cultural practices, and examines the ways in which the text supports and develops what Islam has given women.